ANALISIS PENERAPAN AKAD MUDHARABAH DALAM PRODUK DANA PENDIDIKAN (FULNADI) PADA PT. ASURANSI TAKAFUL KELUARGA CABANG SAKO PALEMBANG - Muhammad Satria Romadhan; Moh. Faizal (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2018)
This study aims to determine the application of the Mudharabah Akad in Education Fund Products (Fulnadi) at PT. Family Takaful Insurance Sako Palembang Branch. In this paper, the author uses field research with qualitative data types using one data source, namely primary data. Data collection techniques are carried out by interviews and documentation that can answer existing problems, and so the data is analyzed descriptively and quantitatively. This result shows the reason why PT. The Sako Palembang Branch Family Takaful Insurance stipulates a mudharabah contract that is used in the Education Fund (Fulnadi) product because the contract does not have a risk on its investment, it is only placed in sharia deposits and Islamic bonds, so there is no risk that causes the participant's education funds to decrease or not be optimal. The application of the mudharabah contract in the Education Fund (Fulnadi) product, must be based on the principle of cooperation between the company and the participants, helping each other if one experiences a disaster, no one gets interest but only gets profit sharing on the investment made by the company, with the Mudharabah agreement. no losses are borne by the participants.